Perforated Meckel's diverticulum - Hadassa Leader; Elizabeth Polott; Jamie M. Pinto; Victoriya S. Staab; Wahid Girgis; Xiu Sun; Srividya Naganathan (Elsevier, 2022)
Acute abdominal pain with fever is a common presentation in the pediatric age group with a wide variety of differential diagnoses. We report a 9 year-old girl with abdominal pain, nausea, diarrhea and fever with exam findings of generalized abdominal tenderness. Her initial evaluation and imaging studies did not reveal the cause of her abdominal pain. Her worsening symptoms and change in physical examination prompted appropriate additional diagnostic workup which revealed a perforated Meckel's diverticulum with peritonitis as the etiology of her symptoms.